Pemanfaatan Instagram Dan Whatsapp Sebagai Media Pemasaran Tenun Medali Mas Kediri - Raharjo, Ari Puji; Tutiasri, Ririn Puspita (Jurnal Ilmiah Wahana Pendidikan, 2024)
The development of this era is increasingly leading to modern times, seen from the rapid development of technology that occurs and humans begin to rely heavily on technology in living their daily lives. The development of increasingly digital technology causes the majority of the world's population to allow access to the internet. In the current era, marketers and consumers are increasingly utilizing dynamic social media as a broad communication channel. Seeing the opportunity to utilize social media as a tool to support and improve marketing functions, the same thing was also done by Tenun Medali Mas Kediri. Digital marketing is an alternative to marketing in this day and age. The method used by the author is descriptive qualitative with data collection techniques through interviews and observations. The results of this study indicate that optimal utilization of social media can have a positive impact on marketing.